Clinical features of patients with multiple myeloma complicated with renal impairment - SHAO Wen; ZHOU Xiao-shuang (Linchuang shenzangbing zazhi)
Objective To analyze the clinical data of patients with multiple myeloma（MM） complicated with renal impairment, and to improve the early diagnosis level of MM complicated with renal impairment to avoid missing diagnosis and false diagnosis.Methods The clinical data of the patients, who were diagnosed as MM in department of hematology and department of nephrology of Shanxi Provincial People’s Hospital Affiliated to Shanxi Medical University, were retrospectively analyzed. According to the diagnostic criteria of acute and chronic renal damage which were developed by International Myeloma Working Group（IMWG） and Kidney Disease Improving Global Guideline Organization（KDIGO）, the patients were divided into normal renal function group and abnormal renal function group. The differences of Clinical features between the two groups were analyzed.Results A total of 296 patients with multiple myeloma were enrolled in this study, and included 95 cases（32.1%） complicated with renal impairment. The average age of the abnormal renal function group was 61.42 years, and the ratio of men to women was 2.06∶1, besides, the serum immunofixation electrophoresis was performed mainly on IgG and IgA. There were no significant differences in age, sex, serum albumin, and total blood κ chain between the two groups. But the incidences of high blood β2-microglobulin（β2-MG）, high blood lactate dehydrogenase（LDH） and hypercalcemia in the abnormal renal function group were significantly higher than those in the normal renal function group, however the hemoglobin concentration in the abnormal renal function group was lower than that in the normal renal function group. In abnormal renal function group, blood β2-MG and LDH levels were negatively correlated with glomerular filtration rate（GFR）. The results of multivariate analysis suggested that the risk of renal function impairment in the patients with MM was increased with the increase of β2-MG, LDH and blood calcium. Conclusions The high levels of β2-MG, LDH and blood calcium in patients with MM are risk factors for MM with renal function impairment. In the meanwhile of application of the traditional test indices, concern about β2-MG, LDH and blood calcium may help detect early renal impairment.